2020
DOI: 10.1108/dlp-02-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

The decay and persistence of web references

Abstract: Purpose The purpose of this study is to identify the persistence and decay of uniform resource locator (URLs) associated with Web references. The decaying of Web references is analyzed in relation to their age, domain, technical errors and error codes. Design/methodology/approach The Web references of the Journal of Informetrics were selected for analysis and interpretation to fulfill the set objectives. The references of all the scholarly articles, excluding editorials and reviews published in the Journal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Wiki Grabber monitors wiki pages and keeps track of wiki pages that have dead links (Grabber, 2021). Further, Loan and Shah (2020) recommended that web sources should be archived in more than one place such as in institutional repositories, subject repositories, national repositories and academic networks to keep them alive and prevent death. The use of LOCKSS (Lots of Copies Keep Stuff Safe)" and CLOCKSS (Controlled Lots of Copies Keep Stuff Safe) can be an efficient tool in this way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wiki Grabber monitors wiki pages and keeps track of wiki pages that have dead links (Grabber, 2021). Further, Loan and Shah (2020) recommended that web sources should be archived in more than one place such as in institutional repositories, subject repositories, national repositories and academic networks to keep them alive and prevent death. The use of LOCKSS (Lots of Copies Keep Stuff Safe)" and CLOCKSS (Controlled Lots of Copies Keep Stuff Safe) can be an efficient tool in this way.…”
Section: Discussionmentioning
confidence: 99%
“…The author reported that only 50.2 per cent of the documents published by the Spanish journal Enfermeria Nefrologica l between 2006 and 2017 were registered by Scopus and the rest weren't indexed in the database. Loan and Shah (2020) studied the persistence, and decay of URLs associated with web references to their age, domain, technical errors and error codes. The results reveal that 32.12 per cent of web references were missing or dead.…”
Section: Review Of Literaturementioning
confidence: 99%